Glucose-6-phosphate dehydrogenase deficiency and the use of primaquine: top-down and bottom-up estimation of professional costs - Henry Maia Peixoto; Marcelo Augusto Mota Brito; Gustavo Adolfo Sierra Romero; Wuelton Marcelo Monteiro; Marcus Vinícius Guimarães de Lacerda; Maria Regina Fernandes de Oliveira (Universidade de São Paulo, 2017)
ABSTRACT The aim of this study has been to study whether the top-down method, based on the average value identified in the Brazilian Hospitalization System (SIH/SUS), is a good estimator of the cost of health professionals per patient, using the bottom-up method for comparison. The study has been developed from the context of hospital care offered to the patient carrier of glucose-6-phosphate dehydrogenase (G6PD) deficiency with severe adverse effect because of the use of primaquine, in the Brazilian Amazon. The top-down method based on the spending with SIH/SUS professional services, as a proxy for this cost, corresponded to R$60.71, and the bottom-up, based on the salaries of the physician (R$30.43), nurse (R$16.33), and nursing technician (R$5.93), estimated a total cost of R$52.68. The difference was only R$8.03, which shows that the amounts paid by the Hospital Inpatient Authorization (AIH) are estimates close to those obtained by the bottom-up technique for the professionals directly involved in the care.